TINJAUAN YURIDIS TENTANG KEWENANGAN PRESIDEN DALAM MEMBENTUK UNIT KERJA PRESIDEN BERDASARKAN PERATURAN PERUNDANG-UNDANGAN - muhammad ridho; Muhammad Amin (Universitas Jambi, Fakultas Hukum, 2021)
Abstract This study aims to determine the limits of the President's authority in establishing the Presidential Work Unit and the relationship between the Presidential Work Units and the legal consequences of the judicial process with other institutions. The results show that, not necessarily because Indonesia adheres to the “supreme constitution,” everything the President does if it is not prohibited (textually) by the constitution is constitutional. It should be understood that we adhere to